Assessing the potential of rural and urban private facilities in implementing child health interventions in Mukono district, central Uganda–a cross sectional study. Issue 1 (December 2016) - Rutebemberwa, Elizeus; Buregyeya, Esther; Lal, Sham; Clarke, Sîan; Hansen, Kristian; Magnussen, Pascal; LaRussa, Philip; Mbonye, Anthony
Abstract Background Private facilities are the first place of care seeking for many sick children. Involving these facilities in child health interventions may provide opportunities to improve child welfare. The objective of this study was to assess the potential of rural and urban private facilities in diagnostic capabilities, operations and human resource in the management of malaria, pneumonia and diarrhoea. Methods A survey was conducted in pharmacies, private clinics and drug shops in Mukono district in October 2014. An assessment was done on availability of diagnostic equipment for malaria, record keeping, essential drugs for the treatment of malaria, pneumonia and diarrhoea; the sex, level of education, professional and in-service training of the persons found attending to patients in these facilities. A comparison was made between urban and rural facilities. Univariate and bivariate analysis was done. Results A total of 241 private facilities were assessed with only 47 (19.5 %) being in rural areas. Compared to urban areas, rural private facilities were more likely to be drug shops (OR 2.80; 95 % CI 1.23–7.11), less likely to be registered (OR 0.31; 95 % CI 0.16–0.60), not have trained clinicians, less likely to have people with tertiary education (OR 0.34; 95 % CI 0.17–0.66) and less likely to have zinc tablets (OR 0.38; 95 % CI 0.19–0.78). In both urban and rural areas, there was low usage of stock cards and patient registers. About half of the facilities in both rural and urban areas attended to at least one sick child in the week prior to the interview. Conclusion There were big gaps between rural and urban private facilities with rural ones having less trained personnel and less zinc tablets' availability. In both rural and urban areas, record keeping was low. Child health interventions need to build capacity of private facilities with special focus on rural areas where child mortality is higher and capacity of facilities lower.